1970
DOI: 10.1097/00006842-197007000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine Excretion: Diurnal Variation and Variability of Whole and Part-Day Measures

Abstract: The stability of creatinine excretion over periods of 4, 8 and 24 hr was studied in 12 subjects, including the 2 investigators; the literature on the subject was critically reviewed. The evidence accumulated shows that creatinine excretion is much less stable than is often assumed. Some subjects are stable excretors as assessed by sequential 24-hr excretion rates, but very few are stable as assessed by sequential rates over periods of less than 24 hr. Not all within-day variability is random. Significant or hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Creatinine excretion rate (g per unit of time) has been shown by several authors to be subject to significant interindividual variations (0.5-3 g/day) as well as intra-day ( ‡200%) and inter-day (63-244%) variations in the same individual (Curtis and Fogel 1970;Greenblatt et al 1976;Boeniger et al 1993). Such variations were also observed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Creatinine excretion rate (g per unit of time) has been shown by several authors to be subject to significant interindividual variations (0.5-3 g/day) as well as intra-day ( ‡200%) and inter-day (63-244%) variations in the same individual (Curtis and Fogel 1970;Greenblatt et al 1976;Boeniger et al 1993). Such variations were also observed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In non-pregnant individuals the CV of creatinine is less than 25%, 23 and on average about 10%, 24 when calculated for a series of only complete 24-h urine collections. Although the CV of creatinine has not been validated for pregnancy, there is no better arbiter of completeness of 24-h urine collections in pregnant women at present.…”
Section: Discussionmentioning
confidence: 92%
“…CR correction is particularly questionable when applied to spot samples because CR excretion over short intervals also shows considerable variation. Verstergaard and Leverett (11 ) showed that subsequent 2-h interval samples varied by Ͼ100%, and several studies have reported that spot-sample CR variation is several times higher than variation for 24-h values (12,13 ). The inap- plicability of CR correction to spot specimens presents a major problem for large prospective studies on reproductive hormones.…”
Section: Discussionmentioning
confidence: 99%